Reproductive responses associated with ram introduction in mature tropical Menz ewes after a period of isolation - Mukasa-Mugerwa, E.; Sovani, S.; Toe, F.; Lahlou-Kassi, A. (Elsevier, 1994)
This study was undertaken using 48 mature Menz ewes (3-6 years of age) and averaging 31.5 (standard deviation (SD)=4.9) kg body weight, to evaluate oestrus synchronization, conception and lambing rates after ram introduction following a period of isolation (n=24) or constant exposure to vasectomized rams (n=24) on a low or high level of nutrition. The overall level of oestrus synchrony was low (27 percent), but was higher for animals previously isolated (38 vs. 17 percent). The mean interval from ram introduction to oestrus was 12.2 (SD=7.3) days, but this was significantly shorter for isolated ewes (9.4+1.2 vs. 14.8+1.7 days, P<0.05). Animals previously better fed were heavier at mating (P<0.01), but this had no relationship to the response to ram stimulation (P>0.05). Oestrus after ram introduction included two peaks (at 6 and 13 days) which were influenced by the behaviour of previously isolated animals. Conception rates to first and second service of 86 percent and 14 percent, respectively, were confirmed by plasma progesterone determinations. Subsequent lambing rate was only 72 percent, suggesting high prenatal reproductive wastage. Lambing was compacted, except for ewes conceiving at their second oestrus. There was as many twins born to isolated ewes as to exposed ewes but substantially more to ewes that were heavier at mating. These data suggest that, although ram introduction after a period of isolation will not increase ovulation and twinning rate in isolated Menz sheep as judged by litter size, it is a natural tool that could be useful to match events of the reproductive cycle of tropical sheep with feed and other management resources.